Haemogram, Organosomastic Indices and Plasma Biochemistry of Clarias gariepinus Injected with Ethanolic Extract of Lepidagathis alopecuroides - , F. G. Obomanu; , U. U. Gabriel; , O. S. Edori (Archives of Current Research International, 2017)
Exposure of organisms to toxicants especially at high concentrations results in changes in biochemical activities of organisms in most cases. Clarias gariepinus were injected with concentrations of Lepidagathis alopecuriodes (2.00, 4.00, 6.00, 8.00 and 10.00 ppm) and a control (0.00 ppm). Precisely 2 ml of the extracts/Kg weight of the fish was used to inject the fish in each of the treatment levels. The control was injected with distilled water. They were allowed to swim freely for fourteen days. Haematological analysis of the fish showed that the parameters did not show any concentration dependent change, though they showed slight effects which were either higher or lower than those of the control value, depending on the parameter examined. Organosomatic indices showed a general decline in the fish condition. There was no observable change in the hepatosomatic and cardiosomatic indices of the fish except at 10.00 ppm dosage in the cardiosomatic index. Significant increase (P<0.05) was observed in the renatosomatic index, while there was observable significant change in the spleenosomatic index. The plasma aspartate transaminase, AST (EC 2.6.1.1) showed a concentration dependent increase in activity except at 4.00 ppm dosage. There was slight uniform (20%) decline in the activities of alanine transaminase, ALT (EC 2.6.1.2) activity in all the dosage concentrations. Alkaline phosphatase, ALP (EC 3.1.3.1) activities declined at 2.00 and 4.00 ppm dosage concentrations, while elevations were observed in all the other dosage concentrations. There was a general decline in the values of sodium ion (Na+) observed in all the dosage concentrations, though not concentration dependent. Potassium ion (K+) and chloride ion (Cl-) did not show any significant change in value with either decrease or increase in their values relative to the control. There was a significant change in the values of hydrogen carbonate ion (HCO3-) which were not concentration dependent. The result of this work showed that the extracts from the plant (Lepidagathis alopecuroides) can cause deleterious effect on fish at high concentrations.